Estudo espectroscópico do íon Eu3+ dopado na matriz de tungstato de estrôncio obtido através do processo sol-gel não-hidrolítico - Pereira, Paula Fabiana dos Santos (2012)
In this work it was investigated the influence of the temperature, time of heat treatment, and the variation of the Eu3+ concentration into the SrWO4 framework related to their structural, morphological and photoluminescent properties. Thus, strontium tungstates, SrWO4, have attracted considerable attention, mainly in the development of researches aiming their utilization as new electro-optic displays, due to their photoluminescent properties. The study of the crystalline scheelite structures promotes the comprehension of their photoluminescent properties. The SrWO4:Eu3+ powders were characterized using the techniques of Thermal Analysis (TG/DTA/DSC), powder X-ray Diffraction (DRX), Rietveld Refinement, Micro-Raman analysis (MR), morphology and determination of the elements by EDSX, absorption in the ranges of ultraviolet-visible (UV-vis.) and infrared (IR), as well as photoluminescence (PL) and lifetime of the Eu3+ ion, X-Ray Photoelectrons Spectroscopy (XPS), and X-Ray absorption (XANES). The TG/DSC analysis showed that the SrWO4:Eu3+ powders were obtained at about 800 oC, being confirmed by XRD, assigned as the scheelite phase of the tetragonal type. The MR and IR spectra indicated only one tetrahedron [WO4] type, and ordering at short distance. The EDSX and XPS analysis indicated the SrWO4:Eu3+ materials are essentially formed by the Sr, W, O and Eu elements presenting, respectively, 2+, 6+, 2- e 3+ as oxidation number. These results were also confirmed by XANES, showing the Eu ion presents 3+ as main oxidation number. The study of the photoluminescent properties showed the electric-dipole 5D0→7F2 transition in the emission spectra is dominant, indicating the Eu3+ ion is positioned in a site without inversion center. The ratios of the 5D0→7F2/5D0→7F1 bands showed the Eu3+ ions are located in a low symmetry environment. The results of emission quantum efficiencies (η) and lifetime (τ) showed a kind of dependence of the temperature effect, time of heat treatment, and variation of the Eu3+ in the SrWO4 framework, indicating the processing conditions at 800 oC and 8 hours are the ideal ones to the obtention of these materials. The sample presenting 2% of Eu3+ showed the higher relative intensity having as well as higher lifetime and emission quantum efficiencies related to the other samples.